Evaluation of some farm structure in South Western Nigeria (2003)
A survey involving the use of questionnaires, personal communication, physical observation and photographic recording was undertaken in South western Nigeria comprising of Ekiti, Ogun, Ondo, Osun and Oyo states to identify the farm structures popularly used; materials used in their construction, their durability and maintenance culture adopted by the users. Farmhouses, cribs, barns, platforms, warehouses, silos, pens, yards and sheds, deep litter houses, palm fronds woven baskets, hutches and cages were the popular farm structures identified. Although a catalogue of materials is available for construction, cost was found to be a major factor in the selection of materials. There was extensive use of locally sourced materials such as wood, natural fibers and earth for the construction of the identified structures. The factors, which tend to reduce the service life and efficiency of these facilities, include roof leaks, abrasion of mud walls, decay and breakage of wooden members, corrosion of metal components, and pitting and cracking of concrete floors. Remedial measures taken include replastering of mud walls and cracked floors, addition of natural fibers to roofs and sealing of leaking points in galvanized roofing sheets, and replacement of broken wood components. These measures where adopted have proved quite useful in improving the efficiency and longevity of the structures. A culture of regular inspection and timely repair of damaged components to prolong the service life and reduce maintenance cost is recommended.